The land availability for private forest development in Gunungkidul Regency, Yogyakarta Province - Utomo, Eko Wahyudi Budhi; Widiatmaka, Widiatmaka; Rusdiana, Omo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
In Gunungkidul Regency, the existing state forest area is relatively fixed and do not allow be extended because the existing land has been used for other cultural activities. Therefore, the existence of private forests in Gunungkidul Regency has a major role because the state forest area that is still far from ideal, ie 9.87% of the total administrative area. The private forest has contributed to the economic and ecological, not only to the owner, but also to the surrounding community. The private forest has great potential, both in terms of the potential of wood produced and the amount of household or labor that could be involved, especially in the rural. The utilization of private forest is a series of business activities which include production, harvesting, marketing / distribution and processing industry. The number of business activities also have implications for the many labor that can be accommodated in a private forest management activities. Land in Gunungkidul still has great potential as a private forest development area. This potential should be identified based on the actual land cover as the basis for private forest development plan. This study aimed to analyze the actual land cover and identify the availability of land as private forest development area. The results showed, land cover in Gunungkidul Regency consists of dry land forest 42,836 hectares, plantations 6,100 hectares, plantations mixture of 3,838 hectares, field 33,096 hectares, shrubs 25,125 hectares, settlements 20,571 hectares, paddy 15,535 hectares, the lake 129 hectares, the river 412 hectares and 26 hectares of coastal shoals. The area available to do the development of private forests covering an area of 55,546 hectares.